STUDY OF PLANT ROOTS ON INCREASING THE SHEAR STRENGTH TO PREVENT SCOURING ON SOIL SLOPE SURFACES OR SHALLOW SLIDES - Aulia, Innocentia Eka; Rusdiansyah, Rusdiansyah (Universitas Lambung Mangkurat, 2023)
The phenomenon of soil scour is influenced by several factors, namely, continuous rainfall, slope, and soil movement. This causes landslides, especially on slope surfaces. The use of vegetation can be used as an effort to overcome shallow landslides on a slope.This study aims to determine the characteristics of the soil, the effect of plant roots on the shear strength of the soil by using a direct shear test tool and to determine the safety value on the slopes by using Geo5 application analysis. The types of plant roots used in this study were Paitan grassroots, Teki grassroots, Setaria grassroots, Gajah grassroots and Alang-Alang grassroots.From the results of the direct shear test, the shear strength value of the soil and Paitan grassroots was 101.433 kg/cm2, the soil with Teki grassroots was 99.392 kg/cm2, the soil with Setaria grassroots2, Alang-Alang grass is 123,730 kg/cm2 and the highest value is found in the soil and Gajah grassroots which is 105,7039 kg/cm2. With the characteristic form of fibrous roots and able to grow to very deep depths, the roots of these plants can have a great impact on soil shear resistance. The greater the diameter and root content in the soil, the greater the shear resistance. The presence of plant roots has proven to be helpful in increasing the holding moment even after erosion has occurred. It can be said that the presence of plant roots on slopes is one of the potential solutions as an effective, economical, and environmentally friendly method. Keywords: shear strength, retaining moment, safety value, plant roots, erosion